Using GIS to Assist in Social Impact Assessments at Military Installations - Darcy Ayers (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2016)
Social Impact Assessments, evolving from NEPA Environmental Impact Assessments, can be used to address societal impacts resulting from large-scale human activities. GIS is a new tool that can be used to assess the spatial distribution of social impacts. This study used GIS and a Dust Impact Index model to identify the populations at risk to dust exposure from a military installation in Hawaii (Pohakuloa Training Area). This analysis is needed due to an Army Stryker brigade transformation that requires more vehicle training, which is resulting in an increase of dust generation. Factors used to determine the Dust Impact Index were wind speed and direction, elevation, and distance from the military installation. The results identified a population to the southwest of the military installation at the highest risk of dust exposure. This project demonstrates the application of geospatial technology as a means to evaluate issues pertaining to environmental anthropology.